Antitumoral activity of Caralluma europaea on colorectal and prostate cancer cell lines. Issue 7 (3rd April 2023) - Samiry, Inass; Pinon, Aline; Limami, Youness; Rais, Samira; Zaid, Younes; Oudghiri, Mounia; Liagre, Bertrand; Mtairag, El Mostafa
ABSTRACT: Caralluma europaea is a medicinal plant used in Moroccan popular medicine, which has been employed as a remedy attributed to its anti-inflammatory, antipyretic, antinociceptive, antidiabetic, neuroprotective, and antiparasitic properties. The aim of the present study was to investigate the antitumor activity of both the methanolic and aqueous extract of C. europaea . The effects of increasing concentrations of aqueous and methanolic extracts on human colorectal cancer HT-29 and HCT116 cell lines and human prostate cancer PC3 and DU145 cell lines were examined on cell proliferation using MTT assay and cell cycle analysis. The induction of apoptosis was also assessed by determining protein expression of caspase-3 and poly-ADP-ribose polymerase (PARP) cleavage by western blot. The methanolic extract of C. europaea exerted significant antiproliferative effects on HT-29 (IC50 values 73 µg/ml), HCT116 (IC50 values 67 µg/ml), PC3 (IC50 values 63 µg/ml) and DU145 cells (IC50 values 65 µg/ml) after 48 hr treatment. Further, incubation with methanolic extract of C. europaea induced cell cycle arrest in G1 phase and an apoptotic process for all treated cell lines. In conclusion, the present results suggest that C . europaea, exhibited that these natural compounds are significant apoptosis inducers which may have considerable potential for development of effective natural product anticancer agents.